Research on odours emitted from non-hazardous waste landfill using dynamic olfactometry - Meišutovič-Akhtarieva, Marija; Marčiulaitienė, Eglė (International Conference “Environmental Engineering”, 2017)
The article analyses the existing research on odour emissions from the passive odour source – municipal landfill for non azardous waste. The current research has been carried out in the Vilnius county, at the Kazokiškės landfill for regional municipal waste. Odour emissions were analysed using samples from waste of different age and at different outdoor air temperatures. The investigation determined the concentration of odourous volatile organic com pounds (VOCs) formed in the landfill (mg/m3) and odour emissions (OUe/m2s). The odour concentration varied between 0.02 OUe/m2s (from 9 year old waste at 11oC) to 1.29 OUe/m2s (from 0–3 year old waste at minus 1 oC and minus 10 oC). It was determined that as temperature decreases (within the range of 11 to minus 10 oC), the concentration of odour emissions increases. The coefficient of correlation between the temperature of environment and the concentration of odours emitted from the landfill stood at minus 0.91.
Keywords: odours; VOCs; landfills; dynamic olfactometry method